TOWARDS SMART PALM OIL MILL FACTORY OPERATIONS USING IR4.0 TECHNOLOGIES - Yap Zheng Yew; Mohamad Taha Ijab; Mohamad Hanif Md Saad, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Palm oil mill industries are commonly found in Malaysia. This is due to Malaysiaâ€™s position as the second leading producer of palm oil worldwide. In 2021, Malaysia supplied a third of the worldâ€™s palm oil next only to Indonesia. Recently, there is a trend of increasing price of palm oil in the market, marking higher demand and higher profitability for the palm oil industry players, including the palm oil mill operators. Towards supporting this greater demand, there are calls for action for palm oil mills to upgrade their â€œstone age technologiesâ€ in order to remain competitive. Sustainability of the operations for future palm oil mills need to be addressed now in line with the drive to adopt new IR4.0 technologies. IR4.0 adaptation in the palm oil mill will create new synergy in production, operation and maintenance management perspective. This paper reviews the current processes in a typical palm oil mill and followed by the potential adaptations of IR4.0 in the existing processes. Five main pillars of IR4.0, namely IoT, big data, cloud computing, machine learning and artificial learning will be discussed in relation to smart palm oil mills of the future. The expected outcomes include increase in the overall production effectiveness, as well as improvement in the administration and maintenance management of smart palm oil mills in the country.